Accumbens volumes are reduced among crack-cocaine users. (3rd April 2017) - Schuch-Goi, Silvia Bassani; Goi, Pedro Domingues; Bermudez, Mariane; Fara, Leticia Schwanck; Kessler, Félix Paim; Pechansky, Flavio; Gama, Clarissa Severino; Massuda, Raffael; von Diemen, Lisia
Highlights: There is a lack of neuroimaging studies that assess different forms of cocaine. Nucleus accumbens volumes in crack-cocaine users and controls are reported. Volumes were significantly reduced among crack-cocaine users, both sides. This may help in targets and strategies for the treatment of crack dependence. Abstract: The brain reward system is known to be the neuroanatomical basis of addictive behaviors. Systemic, cognitive and functional consequences of crack-cocaine addiction are clinically evident, but the neuroanatomical underpinnigs are not yet well understood. We aim to assess the neuroanatomical differences between crack-cocaine patients and paired healthy controls. Fifteen crack-cocaine patients recently discharged from the Addiction Unit of the Hospital de Clínicas de Porto Alegre and fifteen controls matched for gender, age, education and handedness were scanned using a Philips Achieva 1.5T MRI equipment. All subjects had negative positive tests at admission and patients had at least 15 days of detoxification. Active neurologic, inflammatory, cardiovascular or systemic comorbidities were excluded. Subcortical structure volumes were determined using Freesurfer v5.1. Controls had greater volumes in the left accumbens (t = 3.604, df = 28, p = 0.001) compared to patients. Right accumbens volumes were also greater in controls (t = 2.098, df = 28, p = 0.045). Groups did not differ regarding intracranial volumes (p = 0.514). This preliminary and innovative data on crack-cocaine dependence suggests that there is a volumetric reduction of the accumbens, a region that has a significant role in motivation, pleasure, reward and reinforcement learning, and it could play a central role in the pathophysiology of this drug addiction. Therefore, these findings may contribute to understand some behavioral and cognitive deficits in this population.